Single‐marker and haplotype‐based association analysis of anthracnose (Colletotrichum dematium) resistance in spinach (Spinacia oleracea). (10th November 2019) - Awika, Henry O.; Cochran, Kimberly; Joshi, Vijay; Bedre, Renesh; Mandadi, Kranthi K.; Avila, Carlos A.
Abstract: Anthracnose ( Colletotrichum dematium ) is an important disease in spinach ( Spinacia oleracea ). Sources of resistance must be identified, and molecular tools must be developed to expedite cultivar development. In this study, a diverse collection of 276 spinach accessions was scored for anthracnose disease severity. We then evaluated marker identification approaches by testing how well haplotype‐based trait modelling compares to single markers in identifying strong association signals. Alleles in linkage disequilibrium were tagged in haplotype blocks, and anthracnose‐associated molecular markers were identified using single‐SNP (sSNP), pairwise haplotype (htP) and multi‐marker haplotype (htM) SNP tagging approaches. We identified 49 significantly associated markers distributed on several spinach chromosomes using all methods. The sSNP approach identified 13 markers, while htP identified 24 (~63% more) and htM 34 (~162% more). Of these markers, four were uniquely identified by the sSNP approach, nine by htP and nineteen by htM. The results indicate that resistance to anthracnose is polygenic and that haplotype‐based analysis may have more power than sSNP. Using a combination of these methods can improve the identification of molecular markers for spinach breeding.